FAKTOR YANG MEMPENGARUHI PURCHASE INTENTION PADA PRODUK DIOR DIMEDIASI OLEH TRUST - Edy Yulianto Putra; Elinda Nurul Hasana Dewi Binti Shahbi; Ferdinand Nainggolan (POLITEKNIK LP3I JAKARTA, 2024)
The purpose of this study is to examine the variables that affect consumers' inclinations to buy products bearing the Dior brand. by using Trust as a mediator between Perceived Quality, Brand Awareness, Brand Image, eWOM, and Celebrity Endorsement, and Purchase Intention as the dependent variable. 260 respondents were gathered by distributing a Google Form questionnaire to Batam City residents who were acquainted with the Dior brand, which served as the research object. The research findings indicate that, when the variables were tested using the direct effect test, all independent variables had significant results; however, when the variables were tested using the indirect effect test, eWOM did not significantly influence consumers' decisions to purchase Dior brand products. The data was tested using the Smart-PLS application